The influence of school related factors on ICT integration in the management of public secondary schools in Kitui County, Kenya - Mutisya, Angeline Muli; Mwania, Jonathan Muema; Mulwa, David Musyoki (My University, 2017)
The purpose of the study was to determine the influence of school related factors in integration of Information Communication Technology in the management of public secondary schools in Kitui County, Kenya. A descriptive survey research design was used in this study. The study was carried out in 58 public secondary schools in Kitui County that have functional ICT infrastructure. This study used sample size table as proposed by Krejcie and Morgan (1970) whereby 58 principals, 58 senior teachers and 266 assistant teachers from schools that have functional ICT infrastructure were selected. All 16 Sub-county Directors of Education and one County Director of Education were selected for the study. The researcher used questionnaires to collect data from principals, senior teachers and assistant teachers while interview schedule was used to collect data from Sub-county Directors of Education and the County Director of Education in Kitui County. The collected data was analyzed using both quantitative and qualitative data analysis approaches whereby both descriptive and inferential statistics were used. Descriptive statistics that were used in this study include percentages and mean. Hypotheses were tested using Pearson’s moment of correlation coefficient and Pearson’s Chi-square tests for independence. The qualitative data were presented in the form of narrative and integrated within the quantitative data. The findings of the study were; there was a strong positive correlation r(50) = 0.842, p<0.05 between computer infrastructure and ICT integration in management of public secondary schools. The study recommended that; The government should increase their supply of computers to all schools as well as building computer laboratories for schools and that all the schools should have internet connections to enable principals and teachers to use ICT in the school. The government should make it compulsory for all schools to integrate ICT in management.
Keywords: Information communication technology; Public secondary schools; School related factors